Conservation of Brazilian freshwater biodiversity: Thinking about the next 10 years and beyond - Azevedo-Santos, Valter M. [UNESP]; Rodrigues-Filho, Jorge Luiz; Fearnside, Philip M.; Lovejoy, Thomas E.; Brito, Marcelo F. G. (Springer, 2020)
In 2021 the countries of the world will discuss a framework under the Convention on Biological Diversity (CBD) for a new environmental agenda for the next 10 years (post-2020). Parties should consider Brazil to be a central nation in these discussions. The country holds a large freshwater biodiversity that needs to be conserved, but current policies imperil species and ecosystems. Here we present topics to guide other CBD parties in discussing with Brazil a better agenda to conserve freshwater biodiversity post-2020. These initiatives include: (1) a national plan to reduce threats, (2) restoration of freshwater ecosystems, (3) protected areas, (4) more investment in research, and (5) science communication. Brazil's participation in these CBD negotiations is fundamental for a new agreement, but the country is under a presidential administration with little concern for the environment. While our suggestions are intended for participants in the CBD negotiations, they will also be relevant to other international actors in the coming years. Nations, international investors, private companies and NGOs around the world must therefore use their influence to press the current administration to protect the country's environment, including its enormous freshwater biodiversity.
Keywords: Freshwater protected areas; Laws; Mining; Post-2020; Restoration; Biological invasions